Resolution of subclinical porphyria cutanea tarda after hepatitis C eradication with direct‐acting anti‐virals. Issue 10 (15th April 2020) - Sastre, Lydia; To‐Figueras, Jordi; Lens, Sabela; Rodriguez‐Tajes, Sergio; Bartres, Concepció; Aguilera, Paula; Badenas, Celia; Oliva, Rafael; Pocurull, Anna; Forns, Xavier; Mariño, Zoe
Summary: Background: Hepatitis C virus (HCV) is a risk factor for porphyria cutanea tarda (PCT), a rare disease originating in the liver characterised by overproduction of porphyrins. Although hepatitis C infection is highly prevalent among patients with porphyria, only a minority of hepatitis C patients develop PCT. Aims: To explore the presence of porphyrin abnormalities in a cohort of asymptomatic hepatitis C‐infected patients and the impact of anti‐viral therapy. Methods: Eighty‐four consecutive patients with HCV infection treated with direct‐acting antivirals after 1 January 2018 were longitudinally evaluated for the presence of porphyrin abnormalities. Those patients with biochemical abnormalities at baseline were additionally evaluated at follow‐up. Porphyrins in urine were screened by fluorometry and isomer separation was performed by liquid chromatography. Results: In five patients, all of them asymptomatic, porphyrin profile abnormalities were detected: three presented significant increased urinary porphyrins with a typical PCT profile, and two showed normal levels of urinary porphyrins, but abnormal porphyria‐like profiles. Urine evaluation after hepatitis C cure showed complete normalisation of the urinary porphyrins in all patients, confirming the biochemical cure of the disease. Conclusions: We document the existence of rare cases of hepatitis C‐infected patients with significant uroporphyrinuria in the absence of dermatological manifestations. Anti‐viral therapy normalises the biochemical disorder, preventing patients from presenting PCT associated complications.